2021
DOI: 10.1093/ckj/sfab185
|View full text |Cite
|
Sign up to set email alerts
|

Blood-incompatibility in haemodialysis: alleviating inflammation and effects of coagulation

Abstract: Blood-incompatibility is an inevitability of all blood-contacting device applications and therapies, including haemodialysis (HD). Blood leaving the environment of blood vessels and the protection of the endothelium is confronted with several stimuli of the extracorporeal circuit (ECC), triggering the activation of blood cells and various biochemical pathways of plasma. Prevention of blood coagulation, a major obstacle that needed to be overcome to make HD possible, remains an issue to contend with. While anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 118 publications
0
20
0
Order By: Relevance
“…These reductions in regional arterial stiffness may in part result from decreased arterial BP, as BP is known to mechanically increase arterial stiffness. In addition, the reduction in stiffness could result from leukocyte activation as they come into contact with exogenous material from the dialysis membrane, releasing vasoactive mediators associated with vasodilation (Bowry et al, 2021 ). This hypothesis, however, was not directly tested in our study.…”
Section: Discussionmentioning
confidence: 99%
“…These reductions in regional arterial stiffness may in part result from decreased arterial BP, as BP is known to mechanically increase arterial stiffness. In addition, the reduction in stiffness could result from leukocyte activation as they come into contact with exogenous material from the dialysis membrane, releasing vasoactive mediators associated with vasodilation (Bowry et al, 2021 ). This hypothesis, however, was not directly tested in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of inflammation in hemodialysis is multifactorial, and may originate from several sides. Repetitive contact of blood mononuclear cells with dialysis tubes and dialyzer membranes having insufficient biocompatibility may induce inflammation [ 23 , 24 , 25 ]. Complement activating membranes (e.g., cuprophan made membranes) induced the expression of IL-1β and of complement factor 5a (C5a) [ 23 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 , 25 ] Platelet activation is reported to be a component of dialysis biocompatibility. [ 15 ] Aggarwal et al [ 4 ] found continued dialysis decreased platelet activity using flow cytometry to investigate platelet function. The bio-incompatibility character of a low-flux dialyzer may exhaust the platelet more during dialysis and resulted in post-dialytic CEPI prolongation.…”
Section: Discussionmentioning
confidence: 99%